2008
DOI: 10.1103/physrevb.77.085422
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied states of individual silver clusters and chains on Ag(111)

Abstract: Size-selected silver clusters on Ag(111) were fabricated with the tip of a scanning tunneling microscope. Unoccupied electron resonances give rise to image contrast and spectral features which shift toward the Fermi level with increasing cluster size. Linear assemblies exhibit higher resonance energies than equally sized compact assemblies. Density functional theory calculations reproduce the observed energies and enable an assignment of the resonances to hybridized atomic 5s and 5p orbitals with silver substr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 46 publications
10
54
0
Order By: Relevance
“…The STS spectra in Fig. 13.4d acquired from clean Ag(111) surface, monomers (Ag 1 ), dimers (Ag 2 ), trimers (Ag 3 ), tetramers (Ag 4 ), pentamers (Ag 5 ), and a compact silver assembly (Ag n ) with n = 10 show the same trend of the undercoordination-induced polarization [20]. …”
Section: Au and Agmentioning
confidence: 58%
“…The STS spectra in Fig. 13.4d acquired from clean Ag(111) surface, monomers (Ag 1 ), dimers (Ag 2 ), trimers (Ag 3 ), tetramers (Ag 4 ), pentamers (Ag 5 ), and a compact silver assembly (Ag n ) with n = 10 show the same trend of the undercoordination-induced polarization [20]. …”
Section: Au and Agmentioning
confidence: 58%
“…The development of fabrication methods such as the scanning tunneling microscope (STM), electron beam irradiation and mechanically controllable break junctions (MCBJ) have made it possible to investigate metallic nanowires even monatomic metallic chains. Recently, metal monatomic chains have been built by STM manipulation of Au and Pd atoms on a NiAl(110) surface [3][4][5][6], as well as of Cu atoms on Cu(111) surface [7][8][9], and Ag atoms on Ag(111) [10]. The structural and electronic properties of these atomic chains supported on a metal surface have also been investigated theoretically [7,11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies including X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscope/spectroscopy (STM/S) have been used to study the properties of silver and copper NPs, which are observed positive shifts of the core level binding energies and "red" shift of valence local density of states [8][9][10][11]. However, a complete understanding of the underlying mechanisms including size dependence of lattice strain, binding energy shifts, as well as hybridization of Ag [10] and Cu [12] are still lacking.…”
Section: Introductionmentioning
confidence: 99%